OPEN FASCIOTOMY AND PARTIAL FASCIECTOMY AS A CHOICE OF TREATMENT FOR DUPUYTREN'S CONTRACTURE - Margarita Peneva; A. Gjorgjeska; V. Ginoski; S. Tudzarova Gjorgova (Македонско друштво на ортопедите и трауматолозите (МАДОТ), 2016)
Dupuytren's contracture is a benign fibroproliferative disease that affects the palmar and digital fascia of the hand. The condition results in slow and progressive thickening and shortening of the fascia that leads to debilitating flexion contractures. Surgery maintains an important role in the management of the disease. The simplest surgical treatment is open fasciotomy while partial fasciectomy is the most commonly performed procedure for Dupuytran's contracture. It is the preferred method for the treatment of Dupuytran's disease at the University clinic for plastic and reconstructive surgery in Skopje, as well. 150 patients with Dupuytren's disease were treated at the University clinic for plastic and reconstructive surgery in Skopje. The patients were categorized into stages I,II,III and IV as per the severity of the disease. All of them underwent partial fasciectomy and/or open fasciotomy. Open fasciotomy was performed as a single procedure as well as a part of a combined treatment together with partial fasciectomy. The triad of postoperative hematoma, infection and skin loss occured in 3% of the cases. Division of a digital nerve or arteryoccured in less that 1% of the cases. Recurrence is more likely to occur in young patients with strong Dupuytren's diathesis. More than 90% of the patients included in this study had a 100% correction of motion. Surgery for Dupuytren's contracture can give good results. Correct surgical technique and meticulous post-operative care is needed to achieve higher rates of correction.
ОТВОРЕНА ФАСЦИОТОМИЈА И ПАРЦИЈАЛНА ФАСЦИЕКТОМИЈА КАКО ЛЕКУВАЊЕ НА ИЗБОР НА ДИПИТРАНОВА КОНТРАКТУРА
Keywords: Dupuytren's contracture; fasciotomy; partial fasciectomy; surgery